Analisis Pertimbangan Hakim Dalam Menjatuhkan Putusan Nomor: 212/Pid.Sus/2019/Pn.Jmb Terhadap Pelaku Pencemaran Nama Baik Melalui Media Teknologi Informasi - Achmad, Ruben; Supeno, Supeno; Al Nemeri, Muhammad Halik (Legalitas: Jurnal Hukum, 2023)
Defamation (Defamation) is a criminal act of insult (Beleediging) formed by the legislators, both general and specific in nature and is intended to provide protection for legal interests regarding this kind of feeling. The purpose of this study is to understand and analyze the legal considerations of judges in passing decisions on perpetrators of defamation through the media of information technology (Decision Study Number: 212/Pid. Sus/2019/PN.Jmb). To understand and analyze the verdict handed down against the perpetrators of defamation through information technology media (Decision Study Number: 212/Pid. Sus/2019/PN.Jmb) has it reflected justice. The specification of this research is descriptive analytical research. In writing this thesis the author uses the Normative Juridical approach. The legal material in this thesis research was obtained through library research. Based on this consideration it has been proven legally and convincingly that the defendant has committed a crime, then the defendant must be declared guilty and the defendant must be sentenced to a sentence commensurate with his actions which the threat is according to Article 45 paragraph (3) in conjunction with Article 27 paragraph (3) of the Law Republic of Indonesia Number 19 of 2016 concerning Electronic Information and Transactions, the perpetrator is threatened with imprisonment for a maximum of 4 (four) years. However, in this case the defendant was sentenced to 8 (eight) months in prison based on decision Number: 212/Pid.Sus/2019/ PN.Jmb dated 9 May 2019. From a sociological perspective, the sentence of the defendant for 8 months is in accordance with the legal actions carried out by the defendant, although from the point of view of the victim it does not guarantee a sense of justice, it is also less preventive for potential perpetrators of other criminal acts of defamation. Because the sentencing felt so light that the value of the usefulness of the decision was felt to be less acceptable. From a philosophical aspect, to guarantee recognition and respect for the rights and freedoms of others and to fulfill just demands in accordance with security and public order considerations in a democratic society, for the realization of quality, integrity and noble human beings. Suggestions put forward that a judge should have a fair decision in his verdict so that the principle of an independent and impartial judiciary that guarantees the equality of every citizen in law runs well.